Efeito da acidificação da água de bebida de leitões desmamados sobre o desempenho zootécnico e sanitário - Zecchin, Huillian (2023)
The weaning period represents one of the most important stages in pig farming, as it imposes challenges to piglets such as environmental, nutritional and sanitary stress. Aiming to ensure the supply of good quality water to pigs, including reducing the use of antibiotics and controlling enteric challenges, the objective of this study was to evaluate the use of an acidifier used continuously via drinking water on zootechnical performance, intestinal health and hematological parameters of weaned piglets. 1080 female piglets with an average live weight of 6.81 ± 0.29 kg were used, distributed in a completely randomized design consisting of 3 treatments: 1) pH7.39 - natural water pH at 7.39; 2) pH5.31 - pH of drinking water acidified to 5.31; and 3) pH3.40 - pH of drinking water acidified to 3.40; with 8 pens replicates and 45 piglets per pen as the experimental unit. In all treatments the water was chlorinated, within the range of 0.2 to 5 ppm, following the recommendations of Ordinance 888 of 2021 of the Ministry of Health, Brazil. The acidifier used for water treatment in groups 2 and 3 was a commercially available product and recommended as an acidity-regulating additive for drinking water for monogastrics. Its composition is based on ascorbic acid (450.00 mg/kg), citric acid (13.00 g/kg), phosphoric acid (773.50 g/kg) and monosodium phosphate (400.00 mg/kg), nucleotides and palatability agents. The zootechnical indices, water consumption and the oxidation/reduction potential of water were evaluated in the pre-initial phases (from day 1 - 9), Initial I (from day 10-15), Initial II (from day 16 - 30) and total period (from day 1-30), and at the end of the experimental period from 30 days, zootechnical indices, intestinal morphometry and microbiome, biometry of digestive and non-digestive organs, blood gasometry and biochemical profile and blood antioxidant in nursery piglets were evaluated, in addition to the evaluation of the potential of redox of water. The water consumption in the pre-initial phase was higher as the pH of the water decreased and in the initial phase II, the group without acidifiers had the highest average water consumption per animal. The oxidation/reduction (ORP) levels were higher in addition to the amount of acid used. The use of the commercial product did not influence the depth of the villus/crypts in piglets that ingested water with acidifiers. The weight of the stomach, spleen and liver (with gallbladder) of the groups that contained more acidifiers in the water were heavier than the control group, which favored the reduced mortality and influenced some plasmatic levels such as alanine aminotransferase, aspartate aminotransferase and proteins. The study has shown that the animals which received a water diet with the use of chlorinated and acidified water at pH3.40, obtained larger groups of bacterial populations beneficial to the organism when compared to the other groups, which favored beneficial bacteria prevailing the population of Lactobacillus and other bacteria of the Phylum Firmicutes, and inhibited those of the Enterobacteriaceas, showing ability to reduce the load of Escherichia spp. in fecal excretion. In conclusion, it has been recommended the acidification of drinking water at pH 3.40, in order to improve the blood profile and intestinal health, maintaining satisfactory zootechnical performance.